Obesity as a Covered Disability Under Employment Discrimination Law: An Analysis of Canadian Approaches - Zwerling, Harris (Relations industrielles / Industrial Relations, 1997)
Since the passage of the first anti-discrimination laws in North America, the number of groups or classes protected has slowly expanded. People with disabilities are one of the more recent groups to be covered by such laws. No Canadian human rights statute includes the obese or overweight as a separate designated group. British Columbia is the only jurisdiction in which obesity per se has been found to be a covered disability. All other Canadian jurisdictions that have explicitly addressed the issue require claimants to prove that their obesity is a disabling condition and has an underlying involuntary medical cause. This paper examines the treatment of the obese under the antidiscrimination laws of the Canadian federal and provincial jurisdictions, focusing primarily upon the laws of Ontario. Its central thesis is that despite the reticence of various human rights agencies, there is ample legal basis for including obesity as a covered disability under human rights law.